Panorama do debate digital sobre clima no Brasil - Aláfia Lab/*desinformante; Bioversity International and the International Center for Tropical Agriculture; FALA; GEPSCI/UFPB - Grupo de Estudo e Pesquisa em Sociologia; Comunicação e Informação da Universidade Federal da Paraíba Grupo de pesquisa Mídia; Conhecimento e meio ambiente: olhares da Amazônia (UFRR); Grupo de pesquisa Educom Clima (UFSM/CNPq); Instituto Democracia em Xeque (2025)
This report is an initiative of the Brazil Chapter of the Global Initiative for Information Integrity in Climate Change (Rede de Parceiros pela Integridade da Informação sobre Mudança do Clima - RPIIC). It offers an in-depth and systematic analysis of the climate disinformation landscape in Brazil’s digital environment. This document shows that climate disinformation goes beyond the mere spread of fake news; it is a structured phenomenon that operates as a political tool to undermine scientific consensus, erode trust in institutions, and delay effective actions to tackle the climate crisis. Giulia Tucci and Bia Carneiro contributed with a case study in chapter 5.2. A Amazônia em Mensagens: Políticas Públicas e Enquadramentos de Comunicação no Telegram.